2014
DOI: 10.5455/cap.20140714124129
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial Benefits of Physical Activity in Children and Adolescents

Abstract: ÖzetÇocuklarda fiziksel aktivite düzeyi son yıllarda giderek azalmaktadır. Fiziksel aktivitenin azalması, başta obezite olmak üzere pek çok kronik hastalığın erken yaşlarda görülmesine neden olmaktadır. Yaşam boyu fiziksel aktiviteye yeterli katılım ve normal kilonun korunması, obezite, kardiyovasküler hastalıklar, hipertansiyon, Tip II diyabet, akciğer ve kolon kanseri gibi birçok kronik hastalıktan korunmada oldukça etkilidir. Aynı zamanda kendine güvenin, benlik saygısının ve akademik başarı-nın artması ve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
2
4
0
2
Order By: Relevance
“…Apart from these, it can be said that a significant number of participants stated that there was no negative aspect of the fun book. Similar to the above findings, Meydanlıoğlu (2015) emphasized that students should perform significant physical activity outside of school. The findings in this study are consistent with the time emphasis in the study.…”
Section: Discussionsupporting
confidence: 75%
“…Apart from these, it can be said that a significant number of participants stated that there was no negative aspect of the fun book. Similar to the above findings, Meydanlıoğlu (2015) emphasized that students should perform significant physical activity outside of school. The findings in this study are consistent with the time emphasis in the study.…”
Section: Discussionsupporting
confidence: 75%
“…It has been reported that moderate intensity exercise reduces temporary anxiety. In addition, it has been reported to contribute to psychological well-being (Meydanlıoğlu, 2015). In order for students to spend their education and training life healthy and productive, they should be ensured to participate in some sports activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Physical activity not only protects individuals from many chronic diseases such as obesity, cardiovascular diseases and cancer, it also has many psycho-social benefits such as boosting self-confidence, self-esteem, and academic achievement and alleviating the symptoms of depression [5,63]. For these reasons, the society should promote and encourage forming a more active life style and adopting a habit of doing regular exercise, starting with the childhood period [9,64,65]. Increasing the variety of the physical activities and decreasing their difficulty can be a solution.…”
Section: Pedagogics Psychologymentioning
confidence: 99%
“…Many studies conducted state that physical activity strengthen bones and muscles, improve social and psychological health, and enhance fitness level [6,7]. Decrease in physical activity in children and adolescents in recent years has increased the risk of developing many chronic diseases, particularly obesity in early ages [8,9]. On the other hand, physical inactivity is related to numerous health problems including increased risk of heart disease, hypertension, and stroke [10,11].…”
Section: Introductionmentioning
confidence: 99%